Macintosh Computer Viruses: Descriptions and Eradication Methods - Sheila ffolliott (The Canadian Network for Innovation in Education (CNIE), 1989)
Computer viruses and trojan horse programs are computer programs that spread from computer to computer, sometimes (but not always) causing damage to data. Since the people who spread them are usually unaware that they are doing so, computer viruses pose a threat to those who use computers. This article concentrates on detection and prevention of viruses on Macintosh and IBM PC and compatible machines.